Spór o filozoficzne źródła politycznej teorii wojny Carla von Clausewitza. W kręgu interpretacji współczesnych - Damian Winczewski (Historia i Polityka, 2019)
The aim of this article was to discuss basic concepts of Clausewitz philosophy of war. At first, I wanted to present and criticize some older interpretations of philosophical assumptions which founded theoretical schema of On war. In the next part, I presented some recent interpretations based on the distinction between “early” and “old” (or “mature”) Clausewitz. They gave us new look on few theoretical problems included in Prussian’s general works and his attitude to many important Enlightenment philosophers like Kant and Hegel. Finally, I tried to prove that Clausewitz theory has dialectical character, which makes it open and worth further developments.